2016
DOI: 10.1038/jhh.2016.47
|View full text |Cite
|
Sign up to set email alerts
|

The role of compliance with PAP use on blood pressure in patients with obstructive sleep apnea: is longer use a key-factor?

Abstract: Scientific data about the effects of positive airway pressure (PAP) treatment on blood pressure (BP) control are continuously increasing; however, they are controversial. We aimed to determine the long-term effects of compliance with PAP therapy on BP in both hypertensive and normotensive patients with obstructive sleep apnea-hypopnea syndrome (OSAHS). One thousand one hundred sixty eight consecutive patients with newly diagnosed OSAHS, who had been recommended PAP therapy, were followed up for a minimum of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
2
1
Order By: Relevance
“…In previous study, the data was shown of the 2-year effects of CPAP treatment on blood pressure with OSA patients. The mean BMI of previous studies were over 30 kg/m 2 , the study population was different from our study 19 .…”
Section: Introductioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In previous study, the data was shown of the 2-year effects of CPAP treatment on blood pressure with OSA patients. The mean BMI of previous studies were over 30 kg/m 2 , the study population was different from our study 19 .…”
Section: Introductioncontrasting
confidence: 76%
“…The follow up period was 59 months and comprised of 161 patients. In a previous study the 2-year effects of CPAP treatment on blood pressure with OSA patients was shown 19 . The mean BMI of this previous study were over 30 kg/m 2 .…”
Section: Discussionmentioning
confidence: 98%
“…Indeed treatment duration was an independent predictor for favourable BP response to PAP treatment, confirming previous results by Bouloukaki et al . 44 Our data suggest that long-lasting, rather than instant adaptive, processes are operative in OSA-associated hypertension.…”
Section: Discussionmentioning
confidence: 61%